Different methods of pain relief for IVF and ICSI oocyte retrieval – A Dutch survey. (October 2019) - Roest, Inez; Buisman, Erato T.I.A.; van der Steeg, Jan Willem; Koks, Carolien A.M.
Abstract: Objective: Which analgesia methods are used during oocyte retrieval in the Netherlands? StudyDesign: In April 2017, an online survey containing questions on the analgesia protocol used for IVF/ICSI oocyte retrieval was sent to all clinics in the Netherlands that perform oocyte retrievals. Results: The response rate was 97%. We uncovered the large variety of medication protocols used for pain relief during oocyte retrieval in the Netherlands. Based on the main component of the given analgesia, we distinguished the three most frequently used analgesia protocols: intravenously (i.v.) administered opioids, intramuscularly (i.m) administered opioids, and non-sedative oral analgesics. Aside from analgesia, 61% provided anxiolysis with a benzodiazepine. Nearly half of the clinics registered pain scores. The vital functions were monitored at all clinics administering opioids i.v., but at none of the clinics administering opioids i.m. Conclusions: A wide variety of analgesia protocols are used. The three most frequently used are i.v. administered opioids, i.m. administered opioids, and non-sedative oral analgesics. The variety of analgesia protocols is not desirable in the context of good clinical practice, and considering the risks of combining opioids and benzodiazepines. Monitoring of vital functions was only performed after administration of i.v. medication. A comparison of the pain scores could be a first step in finding the optimal method of analgesia, thereby forming the basis of guidelines for analgesia during oocyte retrieval.